Facilitating factors for the establishment of benchmarking partnership in selected clusters - Szydełko, Magdalena (Czynniki sprzyjające nawiązywaniu partnerstwa benchmarkingowego w wybranych klastrach, 2021)
The purpose of the paper is to identify the degree of impact of key internal and external facilitating factors on the establishment of benchmarking partnership in clusters and also to assess the significance of the differences in the results of a survey conducted in this field in a group of selected cluster enterprises and experts. The purpose of the work determined the research procedure which included indirect research focused on the analysis of literature sources and direct research conducted among selected clusters and experts in the form of a survey. The comparative analysis of the impact indicators of individual facilitating factors leads to the conclusion that for the majority of internal and external factors, the strength of the positive impact on the benchmarking partnership was quite similar in the opinion of both representatives of enterprises and experts
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2021; vol. 65, nr 2, s. 159-169